Lenin at the Prague Conference of the RSDRP (January 1912). From: Komplekt nagljadnych materialov po biografi V.I. Lenina - Belousov, P.
Lenin at the Prague Conference of the RSDRP (January 1912). From: Komplekt nagljadnych materialov po biografi V.I. Lenina.